Impact of CYP3A4 functional variability on ziprasidone metabolism - Zhou, Qi; Wu, Yameng; Ye, Zhize; Zhang, Zheyan; Zheng, Kai; Qian, Jianchang; Xiao, Zhongxiang; Lu, Yang (Frontiers in Pharmacology, 2025)
IntroductionZiprasidone is primarily metabolized by CYP3A4, an enzyme with genetic variability and susceptibility to inhibition or induction. This study explored the functional variability of CYP3A4 in ziprasidone metabolism, focusing on drug interactions and genetic polymorphisms.MethodsThe metabolic inhibition and kinetic properties of ziprasidone were evaluated through in vitro experiments utilizing rat liver microsomes (RLM), human liver microsomes (HLM), and CYP3A4 baculosomes. In vivo validation studies were conducted in Sprague-Dawley rats.ResultsQuercetin significantly inhibited ziprasidone metabolism in vitro, with in vivo coadministration led to marked increasing in ziprasidone’s AUC, CLz/F, and Cmax. Inhibition followed mixed mechanisms in RLM, HLM, and CYP3A4.1 systems. Analysis of CYP3A4 variants revealed distinct metabolic efficiencies: CYP3A4.3, 15, and 33 exhibited elevated clearance, while CYP3A4.24, 31, and 34 showed reduced activity. Quercetin’s inhibitory potency varied across alleles, with IC50 values of 17.59 ± 1.01 μM in CYP3A4.1 and 54.51 ± 1.35 μM in CYP3A4.33. Molecular docking identified ARG106, PHE108, PHE215, THR224, and GLU374 as key residues mediating inhibition.DiscussionThe findings of this study underscore the critical role of quercetin-mediated CYP3A4 inhibition and CYP3A4 genetic polymorphisms in modulating ziprasidone metabolism.